Effects of Maternal Vitamin D Supplementation During Pregnancy and Lactation on Infant Acute Respiratory Infections: Follow-up of a Randomized Trial in Bangladesh. (2nd July 2021) - Morris, Shaun K; Pell, Lisa G; Rahman, Mohammed Ziaur; Mahmud, Abdullah Al; Shi, Joy; Ahmed, Tahmeed; Dimitris, Michelle C; Gubbay, Jonathan B; Islam, M Munirul; Kashem, Tahmid; Keya, Farhana K; Mohsin, Minhazul; et al.
Abstract: Background: We examined the effect of maternal vitamin D supplementation during pregnancy and lactation on risk of acute respiratory infection (ARI) in infants up to 6 months of age in Bangladesh. Methods: This study was nested in a randomized, double-blind, placebo-controlled, 5-arm dose-ranging trial of prenatal and postpartum vitamin D supplementation. One group of women received 0 IU vitamin D per week during pregnancy and for 26 weeks post delivery ("placebo" group), one group received high-dose prenatal vitamin D supplementation of 28 000 IU per week and 26 weeks post delivery, and there were 3 additional dose-ranging groups receiving vitamin D supplementation during pregnancy only (4200, 16 800, and 28 000 IU per week, respectively). Episodes of ARI were identified by active and passive surveillance. The primary outcome was microbiologically confirmed ARI, and the primary analysis compared the high-dose prenatal plus postpartum vitamin D vs placebo groups. Results: In total, 1174 mother-infant pairs were included. Among infants born to mothers in the placebo group, 98% had a venous umbilical cord 25(OH)D level below 30 nmol/L compared with none in the high-dose prenatal plus postdelivery vitamin D group. Incidence of microbiologically confirmed ARI in the high-dose prenatal plus postpartum vitamin D (1.21 episodes per 6 person-months; N = 235) and placebo groups (1.07 episodes per 6 person-months; N = 234) was not significantly different (hazard ratio of 1.12 [95% confidence intervals: 0.90-1.40]). There were no differences in the incidence of microbiologically confirmed or clinical ARI, upper, lower, or hospitalized lower respiratory tract infection between high-dose prenatal plus postpartum vitamin D and placebo groups. Conclusions: Despite a high prevalence of maternal baseline vitamin D deficiency and significant effects of maternal vitamin D supplementation on infant vitamin D status, the intervention did not reduce the risk of microbiologically confirmed ARI in infants up to 6 months of age.